A framework for concern-sensitive, client-side adaptation - Firmenich, Sergio Damián
Currently the Web is a platform for performing complex tasks which involve dealing with different Web applications. However, users still have to face these tasks in a handcrafted way. While building "opportunistic" service- based software, such as mashups, can be a solution for combining data and information from different providers, many times this approach might have limitations. In this paper we present a novel approach which combines concern- sensitive application adaptation with user-collected data to improve the user ex- perience while performing a task. We have developed some simple though powerful tools for applying this approach to some typical tasks such as trip planning. We illustrate the paper with simple though realistic examples and compare our work with others in the same field.